Evaluation of Measurement Instruments Using Fuzzy FMEA and MSA/GRR for Determining Calibration Intervals - Asti Ningrum, Vinanda; Bambang Syairudin (UNIPA PRESS, 2026)
Laboratory testing instruments are critical for ensuring accurate measurement results and maintaining product quality. Failures or performance decline in these instruments may affect testing reliability. This study evaluates potential instrument failures using Fuzzy Failure Mode and Effects Analysis (Fuzzy FMEA) and assesses measurement system capability via Measurement System Analysis (MSA) with Gage Repeatability and Reproducibility (GRR). Five instruments Thickness Gauge, Roughness Tester, Tensile Tester, Density Tester, and Chromium Analyzer were analyzed. Fuzzy FMEA results show the Roughness Tester has the highest Fuzzy Risk Priority Number (FRPN = 8.93), followed by the Chromium Analyzer (8.20), Tensile Tester (6.40), Thickness Gauge (5.47), and Density Tester (3.33). Historical data validate that higher FRPN values correspond to more frequent operational failures. GRR analysis indicates all instruments maintain acceptable measurement system performance (%GRR < 30%). Based on these findings, calibration intervals are recommended according to risk level and system stability, promoting efficient calibration management and reliable testing results.